Principal Leadership Strategies in Improving the Quality of Educational Services at SDN 2 Tukasari - Azizah, Kholifatun; Rahayu, Ari; Fiana, Tri; Nurkolis (Lembaga Teewan Journal Solutions, 2026)
Improving the quality of educational services in schools is highly dependent on effective leadership practices implemented by the school principal. This study aimed to analyze the principal’s leadership strategies in improving the quality of educational services at SDN 2 Tuksari. The research employed a qualitative approach with a descriptive design to obtain an in-depth understanding of leadership practices implemented by the principal in enhancing school service quality. The study was conducted at SDN 2 Tuksari, involving the principal, teachers, educational staff, school committee members, and parents as research subjects. Data were collected through interviews, observations, and documentation. The validity of the data was ensured through source triangulation and technique triangulation, while data analysis used the interactive model of Miles, Huberman, and Saldaña, consisting of data reduction, data display, and conclusion drawing. The findings revealed that the principal implemented several leadership strategies to improve the quality of educational services, including strengthening teacher discipline and performance, conducting academic supervision, developing positive school culture, enhancing communication and collaboration, and optimizing educational services. These strategies positively impacted teacher professionalism, learning quality, school climate, stakeholder participation, and educational service effectiveness. The study concludes that effective principal leadership plays a significant role in improving the quality of educational services in elementary schools.